Markets and minds: Trade and value conflicts over biofuels - Sybille Röhrkasten; Claudia Zilla (Stiftung Wissenschaft und Politik (SWP), 2011)
Debates about the production and use of biofuels are emotionally charged and often one-sided, with one group presenting them as a cure-all, the other condemning them out of hand. Assessments of the social and ecological repercussions of biofuel production diverge enormously, and putatively social and ecological criticism sometimes serves as a cover for economic interests. Depending on the competitiveness of their domestic biofuel production, states strive to open up new markets or erect trade barriers to protect their own industries. Finally, the debate is often conducted in idealistic terms, where the pros and cons of biofuels are measured not by the yardstick of empirical comparison with other resources and fuels, but against utopian standards that only few products can hope to satisfy. This study focuses on trade and value conflicts over biofuels, and shall contribute to de-emotionalising the discussion. We outline the positions of the biggest biofuel-producing states, Germany/EU, the United States and Brazil, and analyse their main lines of argument as well as bilateral and multilateral cooperation formats that seek to bridge differences and thus reduce conflict potential
Keywords: 320